If (∀ ε > 0, y ≤ x + ε), then y ≤ x
Let \(x, y ∈ ℝ\). Prove that \[ (∀ ε > 0, y ≤ x + ε) → y ≤ x \]
To do this, complete the following Lean4 theory:
import Mathlib.Data.Real.Basic import Mathlib.Tactic variable {x y : ℝ} example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by sorry
1. Proof in natural language
Let \(x, y\) be real numbers such that \[ (∀ ε > 0)[y ≤ x + ε] \tag{1} \] We will prove, by contradiction, that \(y ≤ x\).
Suppose, for the sake of contradiction, that \[ x < y \tag{2} \] Then, we have: \[ \frac{y - x}{2} > 0 \] And from (1), we know: \[ y ≤ x + \dfrac{y - x}{2} \] Rearranging, we obtain: \[ 2y ≤ 2x + (y - x) \] which simplifies to: \[ y ≤ x \] This contradicts our assumption (2) that \(x < y\).
2. Proofs with Lean4
import Mathlib.Data.Real.Basic import Mathlib.Tactic variable {x y : ℝ} -- Proof 1 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by intro h -- h : ∀ ε > 0, y ≤ x + ε -- ⊢ y ≤ x by_contra! h1 -- h1 : x < y -- ⊢ False have h2 : (y - x)/2 > 0 := by linarith have : y ≤ x + (y - x)/2 := h ((y - x) / 2) h2 have : 2 * y ≤ 2 * x + (y - x) := by linarith have : y ≤ x := by linarith have h3 : ¬x < y := by linarith exact h3 h1 -- Proof 2 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by contrapose! -- ⊢ x < y → ∃ ε > 0, x + ε < y intro h -- h : x < y -- ⊢ ∃ ε > 0, x + ε < y use (y-x)/2 -- ⊢ (y - x) / 2 > 0 ∧ x + (y - x) / 2 < y constructor . -- ⊢ (y - x) / 2 > 0 apply half_pos -- ⊢ 0 < y - x exact sub_pos.mpr h . -- ⊢ x + (y - x) / 2 < y calc x + (y - x) / 2 = (x + y) / 2 := by ring_nf _ < (y + y) / 2 := div_lt_div_of_pos_right (add_lt_add_right h y) zero_lt_two _ = (2 * y) / 2 := congrArg (. / 2) (two_mul y).symm _ = y := mul_div_cancel_left₀ y (NeZero.ne' 2).symm -- Proof 3 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by contrapose! -- ⊢ x < y → ∃ ε > 0, x + ε < y intro h -- h : x < y -- ⊢ ∃ ε > 0, x + ε < y use (y-x)/2 -- ⊢ (y - x) / 2 > 0 ∧ x + (y - x) / 2 < y constructor . -- ⊢ (y - x) / 2 > 0 exact half_pos (sub_pos.mpr h) . calc x + (y - x) / 2 = (x + y) / 2 := by ring_nf _ < (y + y) / 2 := by linarith _ = (2 * y) / 2 := by ring_nf _ = y := by ring_nf -- Proof 4 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by contrapose! -- ⊢ x < y → ∃ ε > 0, x + ε < y intro h -- h : x < y -- ⊢ ∃ ε > 0, x + ε < y use (y-x)/2 -- ⊢ (y - x) / 2 > 0 ∧ x + (y - x) / 2 < y constructor . -- ⊢ (y - x) / 2 > 0 apply half_pos -- ⊢ 0 < y - x exact sub_pos.mpr h . -- ⊢ x + (y - x) / 2 < y exact add_sub_div_two_lt h -- Proof 5 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by contrapose! -- ⊢ x < y → ∃ ε > 0, x + ε < y intro h -- h : x < y -- ⊢ ∃ ε > 0, x + ε < y use (y-x)/2 -- ⊢ (y - x) / 2 > 0 ∧ x + (y - x) / 2 < y constructor . -- ⊢ (y - x) / 2 > 0 field_simp [h] . -- ⊢ x + (y - x) / 2 < y exact add_sub_div_two_lt h -- Proof 6 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by contrapose! -- ⊢ x < y → ∃ ε > 0, x + ε < y intro h -- h : x < y -- ⊢ ∃ ε > 0, x + ε < y use (y-x)/2 -- ⊢ (y - x) / 2 > 0 ∧ x + (y - x) / 2 < y constructor . -- ⊢ (y - x) / 2 > 0 linarith . -- ⊢ x + (y - x) / 2 < y linarith -- Proof 7 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by contrapose! -- ⊢ x < y → ∃ ε > 0, x + ε < y intro h -- h : x < y -- ⊢ ∃ ε > 0, x + ε < y use (y-x)/2 -- ⊢ (y - x) / 2 > 0 ∧ x + (y - x) / 2 < y constructor <;> linarith -- Proof 8 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by intro h1 -- h1 : ∀ ε > 0, y ≤ x + ε -- ⊢ y ≤ x by_contra h2 -- h2 : ¬y ≤ x -- ⊢ False replace h2 : x < y := not_le.mp h2 rcases (exists_between h2) with ⟨z, h3, h4⟩ -- z : ℝ -- h3 : x < z -- h4 : z < y replace h3 : 0 < z - x := sub_pos.mpr h3 replace h1 : y ≤ x + (z - x) := h1 (z - x) h3 replace h1 : y ≤ z := by linarith have h4 : y < y := gt_of_gt_of_ge h4 h1 exact absurd h4 (irrefl y) -- Proof 9 -- ======= example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := by intro h1 -- h1 : ∀ ε > 0, y ≤ x + ε -- ⊢ y ≤ x by_contra h2 -- h2 : ¬y ≤ x -- ⊢ False replace h2 : x < y := not_le.mp h2 -- h2 : x < y rcases (exists_between h2) with ⟨z, hxz, hzy⟩ -- z : ℝ -- hxz : x < z -- hzy : z < y apply lt_irrefl y -- ⊢ y < y calc y ≤ x + (z - x) := h1 (z - x) (sub_pos.mpr hxz) _ = z := by ring _ < y := hzy -- Proof 10 -- ======== example : (∀ ε > 0, y ≤ x + ε) → y ≤ x := le_of_forall_pos_le_add -- Used lemmas -- =========== -- variable (a b c : ℝ) -- variable (p q : Prop) -- #check (absurd : p → ¬p → q) -- #check (add_lt_add_right : b < c → ∀ (a : ℝ), b + a < c + a) -- #check (add_sub_div_two_lt: a < b → a + (b - a) / 2 < b) -- #check (div_lt_div_of_pos_right : a < b → 0 < c → a / c < b / c) -- #check (exists_between : a < b → ∃ c, a < c ∧ c < b) -- #check (gt_of_gt_of_ge : a > b → b ≥ c → a > c) -- #check (half_pos : 0 < a → 0 < a / 2) -- #check (irrefl a : ¬a < a) -- #check (le_of_forall_pos_le_add : (∀ ε > 0, y ≤ x + ε) → y ≤ x) -- #check (lt_irrefl a : ¬a < a) -- #check (mul_div_cancel_left₀ b : a ≠ 0 → a * b / a = b) -- #check (not_le : ¬a ≤ b ↔ b < a) -- #check (sub_pos : 0 < a - b ↔ b < a) -- #check (two_mul a : 2 * a = a + a) -- #check (zero_lt_two : 0 < 2)
You can interact with the previous proofs at Lean 4 Web.
3. Proofs with Isabelle/HOL
theory le_of_forall_pos_le_add imports Main HOL.Real begin (* Proof 1 *) lemma fixes x y :: real shows "(∀ε>0. y ≤ x + ε) ⟶ y ≤ x" proof (rule impI) assume h1 : "(∀ε>0. y ≤ x + ε)" show "y ≤ x" proof (rule ccontr) assume "¬ (y ≤ x)" then have "x < y" by simp then have "(y - x) / 2 > 0" by simp then have "y ≤ x + (y - x) / 2" using h1 by blast then have "2 * y ≤ 2 * x + (y - x)" by argo then have "y ≤ x" by simp then show False using ‹¬ (y ≤ x)› by simp qed qed (* Proof 2 *) lemma fixes x y :: real shows "(∀ε>0. y ≤ x + ε) ⟶ y ≤ x" proof (rule impI) assume h1 : "(∀ε>0. y ≤ x + ε)" show "y ≤ x" proof (rule ccontr) assume "¬ (y ≤ x)" then have "x < y" by simp then obtain z where hz : "x < z ∧ z < y" using Rats_dense_in_real by blast then have "0 < z -x" by simp then have "y ≤ x + (z - x)" using h1 by blast then have "y ≤ z" by simp then show False using hz by simp qed qed (* Proof 3 *) lemma fixes x y :: real shows "(∀ε>0. y ≤ x + ε) ⟶ y ≤ x" proof (rule impI) assume h1 : "(∀ε>0. y ≤ x + ε)" show "y ≤ x" proof (rule dense_le) fix z assume "z < y" then have "0 < y - z" by simp then have "y ≤ x + (y - z)" using h1 by simp then have "0 ≤ x - z" by simp then show "z ≤ x" by simp qed qed (* Proof 4 *) lemma fixes x y :: real shows "(∀ε>0. y ≤ x + ε) ⟶ y ≤ x" by (simp add: field_le_epsilon) end
Note: The code for the previous proofs can be found in the Calculemus repository on GitHub.